Optimal cutting conditions of abrasive waterjet cutting for Ti-6Al-2Sn-4Zr-2Mo alpha-beta alloy using the Aquila algorithm method - Nwankiti, Ugochukwu Sixtus; Oluwo, Adeyinka; Ogunmola, Bayo Yemisi; Rajan, John; Jose, Swaminathan; Oke, Sunday Ayoola; Lathashankar, Boluvar; Ibitoye, Ayomide Sunday (Science, Engineering and Health Studies, 2025)
This article introduces a novel method, namely the Aquila algorithm for optimizing the abrasive waterjet cutting process for machining Ti-6Al-2Sn-4Zr-2Mo alpha-beta alloy. The main parameters of the process are the waterjet pressure (WJP), traverse speed (TS) and the stand-off distance (SOD), while material removal rate (MRR) and surface roughness (Ra) are its responses. The Aquila algorithm optimizes the process parameters, thereby declaring the optimal thresholds for improved efficiency. Unlike previous studies, this work accounts for the optimization of the abrasive waterjet cutting parameters, providing direction on how much of each parameter to utilize for optimal performance of the system. Experimental data from the published literature was used to validate the proposed model. After performing the analysis, the optimal parameters at the convergence of the results after 300 iterations were WJP, TS, SOD, and MRR of 260 bar, 40 mm/min, 3 mm, and 164.74 mm3/min, respectively. This is when the response considered is the material removal rate. Considering the surface roughness as the output, the optimal solutions for WJP, TS, SOD, and SR were 256.27 bar, 24.54 mm3/min, 1.00 mm, and 2.54 mm3/min, respectively. The outcomes will assist process engineers in using optimal results for efficient decision-making in the abrasive waterjet machining process for the Ti-6Al-2Sn-4Zr-2Mo alpha-beta alloy.